Analysis of the Influence of Consumer Behavior on Purchasing Decisions in the E-Commerce Industry - Nasti, Nilawati; Lubis, Ahmad Husin; Rasyid MS, Abdul (International Journal of Economics (IJEC), 2024)
Purchasing decision-making represents a crucial aspect of consumer behaviour prior to the act of purchase. The decision to purchase is made subsequent to an evaluation of the array of available products or services. Online shopping sites appear to offer a convenient and expedient means of fulfilling consumer shopping desires. E-commerce is a commercial activity conducted via the Internet, offering a diverse range of products to consumers. The objective of this research is to ascertain the process by which consumers make purchasing decisions in the context of e-commerce. This research employs a descriptive qualitative approach. This research is situated in the city of Karawang. The informants are four students enrolled in a management studies programme at Buana Perjuangan Karawang University who utilise the e-commerce application on a regular basis. The data was collected through the use of interviews, observation, and documentation. The analysis was conducted by categorising the data into two distinct groups: primary data obtained from direct interviews and secondary data derived from relevant articles. The findings of the study indicate that discount promotions, free shipping promotions, prices, and product quality play a significant role in influencing consumers' online purchasing decisions in e-commerce. The consumer buying decision-making process encompasses five stages: the introduction of needs, information search, evaluation of alternatives, purchasing decisions, and the post-purchase behaviour stage. It can be concluded that students frequently utilise e-commerce platforms to fulfil their needs and desires.